Law relating to virtual worlds. - Chew, Queenie Wan Xiu. (2011)
This study aims to investigate the issues surrounding virtual worlds and ownership of virtual property by examining the 3 important concepts: Economic value, Labour theory and Personality theory. An online survey was conducted to ascertain Singaporean's perception of the rightful owner of virtual property in massively multiplayer online role-playing games (MMORPGs). A total of 340 responses were collected from the online survey portal with 185 responses being utilized for further analysis. This study also reviews the legal systems of several countries which have attempted to award legal recognition to property within the virtual worlds. Drawing on journals, articles and case studies, this paper serves as a starting point for legislators seeking to understand the issues relating to virtual property and may aid in the formulation of laws concerning virtual property in future.